Chemistry of wheat gluten proteins: Quantitative composition. Issue 1 (28th July 2022) - Wieser, Herbert; Koehler, Peter; Scherf, Katharina A.
Abstract: Background and Objectives: Wheat is essential to secure nutrition for the world's population. Its unique processing properties are largely determined by gluten protein content and composition. Findings: Gluten proteins are subdivided into gluten protein types, α‐, γ‐, ω1, 2‐,  and ω5‐gliadins and high‐molecular‐weight glutenin subunits and low‐molecular‐weight glutenin subunits. The overall content and relative proportions of these types vary considerably depending on different genetic and environmental factors and mutual interactions. Conclusion: This review summarizes the latest developments related to the chemistry of gluten and how species and variety, as well as soil type, weather conditions, atmospheric CO2 concentration, diseases, and fertilization with nitrogen, sulfur, phosphorus, potassium, and other minerals affect wheat gluten protein composition. Significance and Novelty: Significant progress has been made to study the effect of different factors on gluten composition. However, comparisons between studies are almost impossible, because of the huge variability in experimental setups, environmental conditions and varieties studied. This calls for a need to develop common guidelines on how to set up experiments, on which parameters to investigate and on which procedure to use to improve comparability and reproducibility of the results.